2010
DOI: 10.1164/rccm.200912-1793oc
|View full text |Cite
|
Sign up to set email alerts
|

The Chitinase-like Proteins Breast Regression Protein-39 and YKL-40 Regulate Hyperoxia-induced Acute Lung Injury

Abstract: Rationale: Prolonged exposure to 100% O 2 causes hyperoxic acute lung injury (HALI), characterized by alveolar epithelial cell injury and death. We previously demonstrated that the murine chitinase-like protein, breast regression protein (BRP)-39 and its human homolog, YKL-40, inhibit cellular apoptosis. However, the regulation and roles of these molecules in hyperoxia have not been addressed. Objectives: We hypothesized that BRP-39 and YKL-40 (also called chitinase-3-like 1) play important roles in the pathog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
119
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 97 publications
(126 citation statements)
references
References 67 publications
7
119
0
Order By: Relevance
“…Retention of GH 18 genes across species and evolutionary time has led to the belief that some of these moieties play essential roles in biology. Recent studies have confirmed this speculation (15,(18)(19)(20)(21), particularly for the prototypic CLP, chitinase 3-like-1 (CHI3L1; also called YKL-40 in humans and BRP-39 in mice). CHI3L1 has been shown by our laboratory and others to play major roles in anti-pathogen, antigen-induced, and oxidant-induced Hermansky-Pudlak syndrome (HPS) comprises a group of inherited disorders caused by mutations that alter the function of lysosome-related organelles.…”
Section: Introductionmentioning
confidence: 85%
“…Retention of GH 18 genes across species and evolutionary time has led to the belief that some of these moieties play essential roles in biology. Recent studies have confirmed this speculation (15,(18)(19)(20)(21), particularly for the prototypic CLP, chitinase 3-like-1 (CHI3L1; also called YKL-40 in humans and BRP-39 in mice). CHI3L1 has been shown by our laboratory and others to play major roles in anti-pathogen, antigen-induced, and oxidant-induced Hermansky-Pudlak syndrome (HPS) comprises a group of inherited disorders caused by mutations that alter the function of lysosome-related organelles.…”
Section: Introductionmentioning
confidence: 85%
“…Initial studies in that area begin in the late 1970s and have started by looking at the combined effect of spasmogens on different measures of lung function in animals (45,46,57,99,102,112,131,152,180,181,192,208,209,224,244), as well as in humans (49,68,97,101,110,156,158,194,202,240). Apart from an interactive synergism at the level of ASM contraction, many other factors can account for these in vivo interactive synergisms.…”
Section: Interactive Synergisms Between Spasmogensmentioning
confidence: 99%
“…in vivo ex vivo in vitro CCh (180) in sheep; HIST (112) in pigs Muscarinic agonists (ACh, MCh or CCh) HIST (158) in humans; HIST (131) and NE (33) in dogs HIST (71), and NE (87,185) in canine tracheal SM strips HIST MCh (158) and HIST (97) in humans MCh (131), ACh (33) and NE (12,33,131) …”
Section: Mediatorsmentioning
confidence: 99%
See 2 more Smart Citations